2014
DOI: 10.5194/amt-7-4299-2014
|View full text |Cite
|
Sign up to set email alerts
|

The use of NO<sub>2</sub> absorption cross section temperature sensitivity to derive NO<sub>2</sub> profile temperature and stratospheric–tropospheric column partitioning from visible direct-sun DOAS measurements

Abstract: Abstract. This paper presents a temperature sensitivity method (TESEM) to accurately calculate total vertical NO 2 column, atmospheric slant NO 2 profile-weighted temperature (T ), and to separate stratospheric and tropospheric columns from direct-sun (DS), ground-based measurements using the retrieved T . TESEM is based on differential optical absorption spectroscopy (DOAS) fitting of the linear temperature-dependent NO 2 absorption cross section, σ (T ), regression model (Vandaele et al., 2003). Separation b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…Strahan et al (2016) demonstrated realistic seasonal and interannual variability of Arctic composition using comparisons to Aura Microwave Limb Sounder (MLS) O 3 and N 2 O. We have found GMI's NO 2 simulation in both the troposphere and stratosphere (Spinei et al, 2014;Marchenko et al, 2015) to be in good agreement with observations.…”
Section: Gmi Modelsupporting
confidence: 71%
See 1 more Smart Citation
“…Strahan et al (2016) demonstrated realistic seasonal and interannual variability of Arctic composition using comparisons to Aura Microwave Limb Sounder (MLS) O 3 and N 2 O. We have found GMI's NO 2 simulation in both the troposphere and stratosphere (Spinei et al, 2014;Marchenko et al, 2015) to be in good agreement with observations.…”
Section: Gmi Modelsupporting
confidence: 71%
“…A new generation of spectroscopic ground-based instruments can measure total (Herman et al, 2009) and tropospheric (Hönninger et al, 2004;Spinei et al, 2014) NO 2 columns at high temporal resolution. The first space-based NO 2 observations started 3134 N. A.…”
Section: Introductionmentioning
confidence: 99%
“…In the stratosphere, NO 2 exhibits significant diurnal variation, with monotonic increase in NO 2 column from~3.0×10 15 molecules cm À2 at 6 A.M. tõ 4.5×10 15 molecules cm À2 at 6 P.M., an increase of 50%. The GMI-simulated diurnal variation of stratospheric NO 2 has been previously evaluated with ground-based multi-function DOAS measurements and reported to agree within 6% [Spinei et al, 2014]. The observed diurnal variation of tropospheric NO 2 is the result of diurnal changes in NO x emissions, PBL mixing, and chemistry.…”
Section: Gmi Simulationmentioning
confidence: 90%
“…In the following, we use effective O 3 cross sections calculated for specific temperatures. This concept was already applied for the retrieval of the total O 3 VCD from satellite measurements of GOME (Hoogen et al, 1999), OMI (Veefkind et al, 2006), and SCIAMACHY (Eskes et al, 2005) as well as for separating stratospheric and tropospheric NO 2 in ground-based direct Sun measurements (Spinei et al, 2014). The calculation of an O 3 cross section for an effective temperature (referred to as effective O 3 cross section (σ e ) in the following) is outlined below.…”
Section: Methods 1: Use Of External Data Sets Of Stratospheric Omentioning
confidence: 99%